Evaluation of External Ear Dermatological Conditions with the Use of Cotton Buds (Medical Forum Monthly, 2021)
Objective: The objective of this study to external ear dermatological conditions with the Use of Cotton Buds in Mirpur AJK.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the department ENT Mohtarma Benazir Bhutto Shaheed Medical College Mirpur AJK and Department of Dermatology Mohi-ud-Din Medical College, Mirpur, AJK from March 2018 to July 2019.Materials and Methods: In this study we selected all those patients which use cotton buds for the cleaning buds and also having dermatological diseases of external ear were including. Those person having not external dermatological diseases of ear are excluded. Those patients having nasal diseases are excluded from the study and also having middle ear diseases is excluded.Results: 209 person using cotton buds for cleaning of ear to remove ear wax and mass in which 174 patients with Dermatological diseases of external disease of external ear (cases) and 35 Non- Dermatological diseases of external disease of external ear 89.22 %) were not aware of injurious effects of use of cotton bud to clean ear. Only 10.53% persons have awareness. Different parentage of external ear infection and dermatological diseases found Neurodermatitis (35.16%) ,Otitis externa (28.57%), Contact dermatitis(25.27%), Wax impaction (7.69%)and Tympanic membrane perforation (3.29%).Conclusion: There is close association of external ear cleaning with demagogical disease when using cotton buds. It is bad and dangerous habit so avoid this.